A comparison of lumbopelvic muscle endurance, stability, mobility, and respiratory functions in children and adolescents with and without nocturnal enuresis. (January 2023) - Karaaslan, Yasemin; Karaaslan, Umut; Celenay, Seyda Toprak
Abstract: Background: Postural deterioration, delayed maturation, and accompanying respiratory diseases in children and adolescents with nocturnal enuresis have been reported in previous studies. This study aimed to compare lumbopelvic muscle endurance, stability, mobility, and respiratory functions in children and adolescents with and without nocturnal enuresis. Methods: Children and adolescents with (n:25, nocturnal enuresis group) and without nocturnal enuresis (n:29, control group) were included. The bladder and bowel dysfunctions with the Bladder and Bowel Dysfunction Questionnaire and voiding diary, lumbopelvic muscle endurance with the McGill trunk muscle endurance tests, lumbopelvic stability with the Sahrmann test, lumbopelvic mobility with the Modified Schober test, and respiratory function with a spirometer were assessed. Independent samples t -test, Mann Whitney U test, and Chi-square tests were used for analysis. Findings: Trunk flexor ( p  = 0.043), extension ( p  = 0.045), and right ( p  = 0.008) and left lateral flexion endurance test scores ( sec ) ( p  = 0.005), the Sahrmann test score (p = 0.005), and Modified Schober test ( p  < 0.001) results were lower in the nocturnal enuresis group compared to the control group. However, there were no differences between groups in terms of forced expiratory volume in 1 s ( p  = 0.415), forced vital capacity ( p  = 0.522), forced expiratory volume in 1 s/ forced vital capacity ( p  = 0.970), and peak expiratory flow values ( p  = 0.495). Interpretation: The children and adolescents with nocturnal enuresis had lower lumbopelvic muscle endurance, stability, and mobility compared to those without nocturnal enuresis; however, the respiratory functions were similar. The lumbopelvic structure changes may be taken into consideration for the management of nocturnal enuresis. Highlights: Lumbopelvic endurance, stability and mobility reduced in nocturnal enuresis. There was no change in respiratory functions in nocturnal enuresis. Lumbopelvic changes should be considered for the management of nocturnal enuresis.